The Increase of Leg Fibrinolytic Potential After Reduction of Hydrostatic Stimulus - Keber, Dušan (Thrombosis and Haemostasis, 1983)
Eleven patients were studied sequentially from the beginning of recumbency due to trauma up to the complete mobilization. The first blood sampling was performed 12 hr to 4 days after injury, the second after 12 to 33 days of recumbency and the third after one or more months of mobilization. The blood was drawn each time before and after venous occlusion of the arm and the leg for 20 min. Fibrinolytic potential was calculated as the difference between post- and preocclusion values of plasminogen activator activity, measured with the euglobulin clot lysis time (ECLT) and on fibrin plates. The results showed that fibrinolytic potential of legs after the period of recumbency was approaching that of the arms, being ten times higher as measured with ECLT and five times higher as measured on fibrin plates in comparison with the period after mobilization. It was concluded that hydrostatic pressure was the main, if not the only factor responsible for the difference in the content of plasminogen activator in veins of arms and legs and their fibrinolytic potential.
Keywords: Plasminogen activator; Mechanism of release; Hydrostatic pressure; Fibrinolytic potential